PtrMYB57 contributes to the negative regulation of anthocyanin and proanthocyanidin biosynthesis in poplar - Wan, Shuzhen; Li, Chaofeng; Ma, Xiaodong; Luo, Keming (Plant cell reports, 2017)
Key message A novel R2R3 MYB transcription factor PtrMYB57 interacted with bHLH131 and PtrTTG1 to form the MBW complex and negatively regulated the biosynthesis of both anthocyanins and PAs in poplar. R2R3-MYB transcription factors (TFs) are important regulators of secondary metabolite biosynthesis in woody species. A series of R2R3-MYB TFs involved in anthocyanin and proanthocyanidin (PA) biosynthesis have been identified in poplar. In this study, we report the identification and characterization of a subgroup 4 MYB member PtrMYB57, which contains a repressor domain (LxLxL) at the C-terminal end. PtrMYB57 encodes an R2R3 MYB protein localized in the nucleus and is predominantly expressed in mature leaves. Transgenic poplar overexpressing PtrMYB57 showed a reduction in anthocyanin and PA accumulation compared to wild-type plants. By contrast, a high anthocyanin and PA phenotype was observed in Ptrmyb57 mutants generated by the CRISPR/Cas9 system. Furthermore, transient expression assays revealed that PtrMYB57 interacted with bHLH131 (bHLH) and PtrTTG1 (WDR) to form the MBW complex and bound to the flavonoid gene promoters, leading to inhibition of these promoters. Taken together, our results suggest that PtrMYB57 plays a negative role in the regulation of anthocyanin and PA biosynthesis in poplar.